An overview of differential mobility analyzers for size classification of nanometer-sized aerosol particles - Panich Intra (2018)
Size classification of nanoparticles is an important process in the electrical mobility particle size analyzer. The differential mobility analyzer (DMA) is one of the most commonly used devices for classifying and measuring nanometer-sized aerosol particles between 1 nm to 1 μm in diameter, based on their electrical mobility. The DMA can be described as an assembly of two concentrically cylindrical electrodes with an air gap between the walls. In the DMA, air and aerosol flows enter from one end, pass through the annulus and exit the other end. An electric field is applied between the inner and outer electrodes. Particles having a specific mobility exit with the monodisperse air flow through a small slit located at the bottom of the inner electrode. These particles are transferred to a particle counter to determine the particle number concentration. In the past several decades, there have been numerous extensive studies and developments on the DMA. Nonetheless, they are different in terms of specific applications, construction, particle size range, as well as time response and resolution. The purpose of this article is to provide an overview of the state-of-the-art existing cylindrical DMAs for aerosol particle size classification as well as for the generation of monodisperse aerosol in nanometer size range. A description of the operating principles, detailed physical characteristics of these DMAs, including the single-channel and multi-channel DMAs, as well as some examples of applications to nanotechnology are given.